2014
DOI: 10.4321/s1886-36552014000300007
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility analysis of genotype-guided antiplatelet therapy in patients with moderate-to-high risk acute coronary syndrome and planned percutaneous coronary intervention

Abstract: BackgroundPrasugrel is recommended over clopidogrel in poor/intermediate CYP2C19 metabolizers with acute coronary syndrome (ACS) and planned percutaneous coronary intervention (PCI), reducing the risk of ischemic events. CYP2C19 genetic testing can guide antiplatelet therapy in ACS patients.ObjectiveThe purpose of this study was to evaluate the cost-utility of genotype-guided treatment, compared with prasugrel or generic clopidogrel treatment without genotyping, from the US healthcare provider’s perspective.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 45 publications
(67 reference statements)
0
24
0
1
Order By: Relevance
“…A total of 66,335 anti-platelet agent initiations over the 4.5 year period were identified. Of them, 33,307 initiated treatment between July 2009 and June 2011, the study period before ticagrelor was approved, and 85% of those cases were clopidogrel users. From July 2011 to the end of 2013, 68%, 25% and 7% of the overall cohort were clopidogrel, prasugrel and ticagrelor initiators, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 66,335 anti-platelet agent initiations over the 4.5 year period were identified. Of them, 33,307 initiated treatment between July 2009 and June 2011, the study period before ticagrelor was approved, and 85% of those cases were clopidogrel users. From July 2011 to the end of 2013, 68%, 25% and 7% of the overall cohort were clopidogrel, prasugrel and ticagrelor initiators, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It is pertinent to understand the clinical and economic implications of genotype-guided prescribing on healthcare systems [36]. A series of previous costeffectiveness studies conducted in the US healthcare setting to understand the economic impact of CYP2C19 genotype testing to guide antiplatelet therapy selection following PCI have focused on longer term (12-15 months and lifetime) outcomes [18][19][20][21][22][23][24]. These studies have collectively concluded that CYP2C19 genotype-guided treatment strategies are cost effective when compared with universal clopidogrel or universal prasugrel treatment without genotype testing.…”
Section: Discussionmentioning
confidence: 99%
“…However, there remains debate and uncertainty surrounding whether a CYP2C19 genotype-guided approach should be routinely used to optimize antiplatelet therapy selection following PCI as a means to improve patient outcomes and lower healthcare costs [17]. A number of recent studies have evaluated the cost-effectiveness of CYP2C19 geno typing for individualized antiplatelet therapy over 12-15 months of treatment [18][19][20][21][22][23][24][25][26]; however, the economic impact on the US healthcare system within the initial 30 days remains unclear. The Patient Protection and Affordable Care Act uses 'quality indicators' to adjust payments to hospitals as part of value-based purchasing [27].…”
mentioning
confidence: 99%
“…To further illustrate this the potential impact of pharmacogenomics in precision medicine, some individuals with specific CYP2C19 gene mutations are poor metabolizers of the clopidogrel prodrug (the most commonly used antiplatelet agent), which can limit safety of coronary stents after percutaneous coronary intervention [7]. Some studies have demonstrated the possible cost-effectiveness of genotype-guided antiplatelet strategy [126][127][128][129], underscoring the potential utility of precision medicine to tailor medication regimens and achieve optimal patient care. In the genotype-guided antiplatelet strategy, antiplatelet utilization following acute coronary syndrome (ACS) and percutaneous coronary intervention (PCI) would be determined based on CYP2C19 genotype obtained prior to the procedure.…”
Section: Clopidogrelmentioning
confidence: 99%